Penyuluhan Hukum Mengenai Fenomena Ajakan Gagal Bayar (Galbay) dalam Pinjaman Online - Suwandono, Agus; Yuanitasari, Deviana; Harrieti, Nun (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The phenomenon of encouraging online loan default is rampant on social media and has become a trend among online loan consumers in Indonesia. Encouraging people not to pay their online loans by defaulting is an illegal act that has the potential to harm fund recipients, fund providers, and online loan companies, thus necessitating legal understanding of online loans through legal education activities. The legal education method used in this community service initiative employs a Participatory Action Research (PAR) approach, aimed at providing legal understanding of the phenomenon of loan default in online lending to protect consumers in the financial services sector. The results of the community service activities through legal education have improved legal understanding of the legal aspects of loan default in online lending. Default actions taken by consumers will not resolve their online loan issues but may instead lead to legal consequences and risks for the consumers themselves. Consumers facing difficulties in repaying online loans should not default. Instead, they should resolve their issues by contacting the online lending company through complaint and dispute resolution mechanisms in accordance with consumer protection regulations in the financial services sector.